Molecular Characterization of Nannochloropsis sp. Based on tufA Genetic Marker and Potential Test of Nannochloropsis sp. as a Cadmium (Cd) Heavy Metal Bioremediation Agent - Sulis Setyowati; Hermin Pancasakti Kusumaningrum; Muhammad Zainuri; Agung Suprihadi; Heradita Kaniaazzahra Doktorasaintifika; Azalia Puspa Herida; Candra Wahyuningsih; Siti Nur Jannah; Wijanarka Wijanarka (Buletin Oseanografi Marina, 2025)
Cadmium (Cd) heavy metal pollution not only affects aquatic ecosystems but also has toxic effects on human health. Bioremediation using microalgae Nannochloropsis sp. is considered more economical and sustainable for overcoming heavy metal pollution. This study aims to molecular characterization of Nannochloropsis sp. with tufA gene markers, determine the effect of different Cd concentrations on the growth and morphology of Nannochloropsis sp. and the ability of Nannochloropsis sp. to absorb Cd concentrations. The methods used include DNA isolation, quantitative and qualitative DNA analysis, amplification of tufA gene, sequencing result analysis, phylogenetic tree analysis, and bioremediation test. The results of molecular characterization showed that Nannochloropsis sp. has similarities with N. oceanica strain BR2 plastid (CP044614.1) with 60% bootstrap value. Nannochloropsis sp. grew at different Cd concentration (0, 2, 4, and 6 ppm) but optimal at 0 ppm Cd concentration. Morphology of Nannochloropsis sp. showed morphological differences in the cell structure. The cell was broken and the color turned increasingly clear. Different concentrations of Cd metal on Nannochloropsis sp. growth significantly affected the decline in Nannochloropsis sp. growth. Nannochloropsis sp. has the potential to absorb heavy metal Cd with an efficiency that increases as the concentration reaching 62.6% at 6 ppm. It can be concluded that molecular characterization using the tufA marker was effective in showing that Nannochloropsis sp. had closed relation with N. oceanica strain BR2 plastids. Cadmium (Cd) exposure significantly reduced growth and caused cell damage, while Nannochloropsis sp. effectively adsorbed Cd and lowering Cd levels by 3.76 ppm.